2009
DOI: 10.1098/rsbl.2009.0540
|View full text |Cite
|
Sign up to set email alerts
|

Evicting cuckoo nestlings from the nest: a new anti-parasitism behaviour

Abstract: As avian brood parasitism usually reduces hosts' reproductive success, hosts often exhibit strong defence mechanisms. While such host defences at the egg stage (especially egg rejection) have been extensively studied, defence mechanisms at the nestling stage have been reported only recently. We found a previously unknown anti-parasitism behaviour in the large-billed Gerygone, which is a host species of the little bronze-cuckoo, a host-evicting brood parasite. The hosts forcibly pulled resisting nestlings out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 13 publications
2
135
0
2
Order By: Relevance
“…Second, gerygones may recognize foreign eggs, but choose to act on this recognition only later in the nesting cycle. Large-billed gerygones sometimes reject little bronze-cuckoo chicks from their nests [13], despite nestling cuckoos being good mimics of gerygone young [31]. Delaying rejection until the chick stage may occur, because there are physical constraints on gerygones removing eggs larger than their own ( [32], but see [33]) or because retaining cuckoo eggs in the nest has the beneficial effect of diluting the risk of further gerygone egg loss should the nest suffer subsequent parasitism [14,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, gerygones may recognize foreign eggs, but choose to act on this recognition only later in the nesting cycle. Large-billed gerygones sometimes reject little bronze-cuckoo chicks from their nests [13], despite nestling cuckoos being good mimics of gerygone young [31]. Delaying rejection until the chick stage may occur, because there are physical constraints on gerygones removing eggs larger than their own ( [32], but see [33]) or because retaining cuckoo eggs in the nest has the beneficial effect of diluting the risk of further gerygone egg loss should the nest suffer subsequent parasitism [14,34].…”
Section: Discussionmentioning
confidence: 99%
“…Large-billed gerygones are not reported to reject cuckoo eggs [13], but it is unknown whether this is, because the eggs are cryptic, or because these hosts lack defensive egg rejection altogether [14]. Multiple parasitism of large-billed gerygone nests occurs regularly, and genetic analysis has confirmed that this is due to laying by multiple females rather than maladaptive repeat laying by a single female [8].…”
Section: Introductionmentioning
confidence: 94%
“…Recordings were made using a directional microphone Sennheiser ME 66 connected to a digital audio recorder Edirol R-09, at a sampling rate of 44.1 kHz stereo (16 …”
Section: Methodsmentioning
confidence: 99%
“…and Chrysococcyx minutillus) and their hosts have shown that host parents were able to reject parasitic chicks either through the desertion of parasitized nests soon after hatching [15] or active eviction of parasitic young out of the nest [16,17], and later work suggests that host rejection behaviour, in turn, may have selected for reciprocal host chick mimicry in bronzecuckoos [15,18]. These findings have challenged prior theoretical arguments that learned chick discrimination would be maladaptive in hosts of evictor brood parasites such as cuckoos [19] (see also [20]) and suggest that a coevolutionary arms race similar to that observed at the egg stage may also occur at the nestling stage [15][16][17] (but see [21]). Visual mimicry of host chicks has also been reported in parasitic finches (Vidua sp.…”
Section: Introductionmentioning
confidence: 99%
“…Because this misimprinting hypothesis was proposed to explain the absence of adaptation, it cannot be tested directly, but two corollary predictions are testable in species that do show offspring recognition: first, chick recognition can be an effective host defense when reliable information is available, and second, such recognition would involve learning. 7, 10 Two definitive cases of chick recognition have recently been documented; 4,13,18 however, although previous experience honed host rejection abilities in one of these hosts, 4 the learning mechanisms have yet to be elucidated. Here we confirm the corollary predictions of the misimprinting hypothesis in an unlikely system-brood parasitism within species-and describe the learning mechanism involved in chick recognition.…”
Section: Introductionmentioning
confidence: 99%